2002
DOI: 10.1177/009164710203000206
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Intrinsic Religion as a Source of Universal Compassion

Abstract: Several studies have considered the ability of devout Christians to accept homosexual persons while rejecting homosexual behavior. Batson, Floyd, Meyer, and Winner (1999) found that intrinsic Christians were not able to make that distinction. Bassett et al. (2000) found that intrinsic Christians were able to distinguish between the value of homosexual persons and behavior. Both studies used financial help as the measure of acceptance. This study replicated the Batson et al. methodology with some modifications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Bassett and his colleagues have addressed this limitation by investigating Christian participants' reactions to gay people who are celibate versus gay people who are sexually active. Bassett et al (2002) adopted a role‐play version of Batson et al's (1999) methodology. In their study, the discloser indicated either that he/she was celibate and gay, sexually active and gay, or sexual orientation was not mentioned.…”
Section: Prejudice and Value‐violationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bassett and his colleagues have addressed this limitation by investigating Christian participants' reactions to gay people who are celibate versus gay people who are sexually active. Bassett et al (2002) adopted a role‐play version of Batson et al's (1999) methodology. In their study, the discloser indicated either that he/she was celibate and gay, sexually active and gay, or sexual orientation was not mentioned.…”
Section: Prejudice and Value‐violationmentioning
confidence: 99%
“…Some behavioral research has found that devout, intrinsically religious individuals are equally prejudiced against a gay person who engages in behavior that might violate religious values, and one who does not (Batson et al 1999). Other self‐report studies suggest that the intrinsically religious may treat gay people differently depending on the sexual activity of the gay person (Bassett et al 2002; Fulton, Gorsuch, and Maynard 1999). Because a homosexual orientation might imply sexual behavior outside of the traditionally defined marriage relationship, it may be difficult to separate negative attitudes toward gay men and lesbians from negative attitudes toward extramarital sexual behavior.…”
mentioning
confidence: 99%
“…Those high in extrinsic personal motivation may participate in religious activities to be seen as a good person or to avoid condemnation by God. Bassett et al (2002) found that intrinsically oriented Christians were equally willing to help a celibate gay person as they were a heterosexual person. In their study, the celibacy of the individual seemed to be an important determinant of the intrinsically religious participant's willingness to help.…”
Section: Religious Orientationmentioning
confidence: 98%
“…Some of these religious individuals believe that individuals, including homosexual adults, are controlled or influenced by Satan or evil spirits (Wilson & Huff, 2001). Some religious individuals espouse a position of hating the sin, but loving the sinner, and they assert that moral evaluations do not necessarily represent prejudice (Bassett et al, 2002;Fulton et al, 1999). However, gay men and lesbians often experience this position as comparably homonegative to directly discriminatory positions (Maynard & Gorsuch, 2001).…”
Section: Religion and Homonegativitymentioning
confidence: 99%
“…Over the past 20 years, several studies have addressed the adage "love the sinner and hate the sin" (e.g., Bassett et al, 2002;Batson, Floyd, Meyer & Winner, 1999;Fulton, Maynard & Gorsuch, 1999;Mak & Tsang, 2008;Rowatt, LaBouff, Johnson, Froese & Tsang, 2009;Veenvliet, 2008). Most of the research has evaluated the degree to which certain religious people, Christians in particular, might be able to do it -maintain positive sentiment for someone who is associated with a behavior that is considered negative, inappropriate, and morally wrong.…”
Section: Introductionmentioning
confidence: 99%